PENENTUAN KADAR FLAVONOID TOTAL DAN NILAI SPF EKSTRAK ETANOL DAUN BUAS-BUAS (Premna serratifolia L.) ASAL KABUPATEN MELAWI PROVINSI KALIMANTAN BARAT - Weni Puspita; Heny Puspasari (Universitas Wahid Hasyim Semarang, 2021)
ABSTRACT Premna serratifolia L. leaves contain flavonoids, saponins, polyphenols, and terpenoids, potentially act as sunscreens. The purpose of this study was to determine the flavonoid content and SPF (Sun Protection Factor) ethanol extract of Premna serratifolia L. leaves from Melawi Regency, West Kalimantan Province using UV-Vis spectrophotometer. The Premna serratifolia L. leaves were extracted by maceration using 70% ethanol solvent, then the filtrate obtained was concentrated with a rotary vacuum evaporator to obtain a thick extract. The extract was determined for its flavonoid content using UV-Vis spectrophotometer at a wavelength of 439 nm, and the SPF value was determined at a concentration of 25, 50, 75, and 100 ppm with a UV-Vis spectrophotometer at a wavelength of 290-320 nm. The SPF value was calculated and analyzed descriptively using the Mansur method. The result showed that the average flavonoid content of ethanol extract of Premna serratifolia L. leaves was 3.70±0.02% calculated as quercetin. The SPF EEDB values obtained from variations in concentrations of 25, 50, 75, and 100 ppm respectively were 19.95±0.02; 30.08±0.01; 34.58±0.14; and 38.28 ± 0.12, where the SPF value is included in the ultra protection category. Key words: Premna serratifolia L. leaves, flavonoid content, SPF, UV-Vis Spectrophotometer